(Invited) Process and Integration of Dielectrics Required for 10nm and Beyond Scaling. (26th April 2016) - Clark, Robert D.; Tapily, Kandabara; Consiglio, Steven; Hakamata, Takahiro; O'Meara, David; Newman, Daniel; Collings, Michael; Szymanski, Dennis; Wajda, Cory S.; Leusink, Gert J.
Abstract : Dielectric materials with tailored properties are required to meet future device and integration needs. Deposition processes that are self-limited (e.g. Atomic Layer Deposition (ALD)), or self-directed (e.g. selective deposition) will enable those materials to be used in scaled 3D devices incorporating new channel materials. Highly tailored ALD processes are being investigated to fabricate functional material layers. Interspersed treatments and doping to make ternary materials may be used to modify the physical and electrical properties of ALD films further in order to optimize the resulting physical or electrical properties. Examples of these and similar processes are described and discussed with the goal of discerning a path beyond 10nm devices.